BIODIVERSITY CONSERVATION IN THE EXPLOITATION OF NATURAL RESOURCES IN INTERNATIONAL SEABED AREAS UNDER THE BIODIVERSITY BEYOND NATIONAL JURISDICTION AGREEMENT - Ihdal Umam; Risnain, Muh; Zunnuraeni (Mataram Journal of International Law, 2024)
This research aims to analyze and understand the conservation of biodiversity in international seabed areas based on BBNJ, and to analyze the urgency of the State of Indonesia to ratify the BBNJ Agreement. The research method used is normative legal research. The results show that conservation in the context of the BBNJ (Biodiversity Beyond National Jurisdiction) Agreement includes protection and conservation of natural resources and management. Protection and conservation are regulated through the establishment of area-based management instruments and the requirement of environmental impact assessments for activities on the high seas and the international seabed. Meanwhile, conservation within management is addressed through equitable benefit sharing, technology transfer and capacity building. Therefore, the ratification of the BBNJ Agreement is very important for Indonesia because Indonesia's geographical situation as an archipelago with a large marine area requires effective protection of marine biodiversity, most of which is beyond national jurisdiction. Ratification of the BBNJ Agreement will strengthen national capacity in marine technology, provide better access to marine genetic resources, and strengthen Indonesia's commitment to sustainable ocean management and contribute positively to global ocean governance.